HISTORY OF INNOVATION IN MUSIC: संगीत में नवाचार का इतिहास - Pawar, Vasundhara (International Journal of Research -GRANTHAALAYAH, 2015)
The history of Indian music is as ancient and eternal as mankind. Its Sankarancha is considered Vedic. The music and culture of our country is as ancient as the ancient civilization and culture of our country. Indian music originated from the deities of Samadeva and its infancy was spent in the meditation of the taphbhoomi of the sage sages and the sacred groves of the Yajnavedis. This is the reason why the Indian mystics have described Naad as God, and Naad has always worshiped the universe. भारतीय संगीत का इतिहास उतना ही प्राचीन और अनादि हैं, जितनी मानव जाति। इसका सभारंच वैदिक माना जाता है। जितनी प्राचीन हमारे देश की सभ्यता और संस्कृति है उतना ही विस्तृत एवं विषाल यहाँ के संगीत का अतीत है। भारतीय संगीत का उद्भव सामदेव की ऋचाओं से हुआ है तथा इसका शैषव काल ऋषि मुनियों की तपोभूमि तथा यज्ञवेदियों के पावन घ्रुम के सान्निध्य में सुवासित होकर व्यतीत हुआ। यही कारण है कि भारतीय मनीषियों ने नाद को ईश्वर के समान कहा गया है, तथा नाद ब्रह्य की सदैव उपासना की है।